ARABIC- DISSOLUTION OF MARRIAGE ON GROUNDS OF INSOLVENCY OF HUSBAND: A COMPARATIVE STUDY BETWEEN FQIH-UL-ISLAMI AND PAKISTANI LAW - Muhammad Ramzan; Shabbir Ahmad (دی اسکالر)
Islamic law has granted countless rights to the women by ending up their exploitation. One for the most significance rights is her right of dissolution of marriage in case her husband is failed to pay her maintenance. In this scenario, the researcher has comparatively analyzed Islamic law and Pakistani law by answering the question: Dose the women has the right of dissolution of her marriage when her husband could not fulfil her maintenance? After the arguments and discussions, the study leads to the conclusion that the woman has the right to ask the court to dissolve her marriage when she unable to have her maintenance from her husband’s side so that she may not has to bear the burden of insolvency without any logical reason. The study also reveals that before the promulgation of Islam when the women’s rights were being condemned and violated everywhere, Islam was the only religion which raised the voice for protection of women’s rights and bestowed them respectable position in community by providing them their legal rights. Moreover, the study is the rejection of invalid objection for the enemies of Islam that Islam has demonstrated invidious reservation in the case of women’s rights by showing biasness.